Mobile learning development of games based model using RPG Maker MV in ecosystem concept - I Aripin (Pascasarjana Universitas Pendidikan Indonesia, 2018)
The purpose of this research is to develop learning media based on mobile learninggames model on biology learning that is feasible and practical to use. This research usesresearch approach and development approach (R & D) with model of development of ADDIE (Analyze, Design, Development and Evaluation). Media developed using RPG Maker MVsoftware with learning materials of ecosystem concept. The data of research was collectedusing questionnaire for assessment by media expert, material expert, observation sheet,assessment sheet and concept of mastering test. The next data was analyzed qualitatively andquantitatively using SPSS v.21 software. Based on the results of research indicates that themedia developed according to the assessment of media expert, material expert and userpertained feasible to used with high category. The result of activity observation and userresponse in learning using mobile learning model categorized by high means that most studentsfocus and enthusiastic on learning. The results of the implementation of media usage measuredfrom the mastery of student concepts show that mobile learning games model are able toincrease the mastery of students concepts on ecosystem materials.